2015
DOI: 10.2174/1389201016666150907113653
|View full text |Cite
|
Sign up to set email alerts
|

The Past, Present and Future Subclassification of Patients with Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is characterized as a heterogeneous disease where the patients are sub grouped according to several classification systems and mutational analyses. Diagnosis of AML is based on identification of the specific myeloid cell initiating the disease, quantification of immature blasts in bone marrow and peripheral blood, as well as detection of mutations and translocations. The heterogeneity of AML is caused by a block in differentiation that may occur in any of the different myeloid cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…AML represent a heterogeneous group of hematological disorders best categorized by their cytogenetic characteristics and mutational status 35 36 37 . Previous studies have shown that higher expression of PCNA in blast cells was correlated with blast cell percentage in myelodysplastic syndromes and in relapsed AML but no information on PCNA localization was provided 38 .…”
Section: Discussionmentioning
confidence: 99%
“…AML represent a heterogeneous group of hematological disorders best categorized by their cytogenetic characteristics and mutational status 35 36 37 . Previous studies have shown that higher expression of PCNA in blast cells was correlated with blast cell percentage in myelodysplastic syndromes and in relapsed AML but no information on PCNA localization was provided 38 .…”
Section: Discussionmentioning
confidence: 99%